Application of Thermal Imaging and PWC170 - Zuzda, Jolanta (2019)
The aim of this paper is to verify whether step aerobics training (SAT) has an impact on the temperature of deep muscles of the spine of young, healthy subjects and if there exists a relationship between the maximal oxygen uptake (VO2max) and thermal results. The study was conducted in a group of 21 subjects of both sexes, aged 20.2 ± 0.38. The step aerobics training sessions lasted 30 weeks, one training session per week, 60 minutes per session. Thermograms of the spine were taken with the use of an infrared thermographic camera. Instrumental measurements included BMI, vital capacity of the lungs, and maximal oxygen uptake (VO2max). After a 30-weeklong SAT, a statistically significant increase in the average temperature of the muscles of the thoracic and lumbar spine was observed in subjects of both sexes (1.2◦C and 1.28◦C, respectively, p < 0.05). At the same time, VO2max increased from 42.98 ml/kg/min to 43.6 ml/kg/min in male subjects and from 40.4 ml/kg/min to 41.1 ml/kg/min in female subjects (p > 0.05). The relationship between VO2max and temperature of the muscles of the thoracic and lumbar spine after the 30th SAT was not statistically significant (r = - 0.28; p = 0.226; r = - 0.11; p = 0.634, respectively). The study showed that a 30-weeklong step aerobics training (SAT) had a positive impact on thermoregulation of apparently healthy male and female subjects aged 20. Furthermore, it can be safely assumed that thermography may be used as a non-invasive method of examination of the thermoregulation mechanism of SAT participants.